Catalytic α-Arylation of Ketones with Heteroaromatic Esters - Isshiki, Ryota; Takise, Ryosuke; Itami, Kenichiro; Muto, Kei; Yamaguchi, Junichiro (Synlett, 2017)
Heteroaromatic esters were found to be applicable as an arylating agent for the Pd-catalyzed α-arylation of ketones in a decarbonylative fashion. The use of our in-house ligand, dcypt, enabled this unique bond formation. Considering the ubiquity and low cost of aromatic esters, the present work will allow for rapid access to valuable α-aryl carbonyl compounds.
Keywords: α-arylation; aromatic esters; decarbonylative coupling; palladium; heteroarenes; ketones